The graveyard book - Gaiman, Neil.; McKean, Dave (New York : HarperCollins, 2008)
The orphan Bod, short for Nobody, is taken in by the inhabitants of a graveyard as a child of eighteen months and raised lovingly and carefully to the age of eighteen years by the community of ghosts and otherworldly creatures.
Newbery Medal/Honor.
School Library Journal.
Wilson's Children.
Booklist starred, September 2008.
Bulletin (Center for Children's books), October 2008.
Horn Book Starred, November 2008.
Keywords: Cemeteries -- Juvenile fiction; Dead -- Juvenile fiction; Supernatural -- Juvenile fiction; Cemeteries -- Fiction; Dead -- Fiction; Supernatural -- Fiction; Cemeteries -- Fiction; Death -- Fiction; Supernatural -- Fiction